Gestural communication in nonhuman and human primates - Liebal, Katja; Müller, Cornelia; Pika, Simone (Benjamins current topics ;, 2007)
Research into gestures represents a multifaceted field comprising a wide range of disciplines and research topics, varying methods and approaches, and even different species such as humans, apes and monkeys. The aim of this volume (originally published as a Special Issue of Gesture 5:1/2 (2005)) is to bring together the research in gestural communication in both nonhuman and human primates and to explore the potential of a comparative approach and its contribution to the question of an evolutionary scenario in which gestures play a significant role. The topics covered include the spontaneous n.